Reforma al código orgánico integral penal que incorpore el delito de enriquecimiento ilícito por la defraudación tributaria - Cerda Shiguango, Stalin Wilmer (2017)
The current Code of Criminal Integral responds to a social need for change in the criminal justice system and the administration of justice, however, two years of its implementation, even some crimes that have not been considered in the same evidence. COIP said, in Book I, Title IV, Chapter V, Section Three, Article 279, - for illicit enrichment, states:  The or public servants and persons acting under a state power in one of the institutions of the state, determined in the Constitution of the Republic, who have obtained for himself or others an unjustified increase in assets to its name or by intermediary product of their position or function.  It is understood that not only were illicit enrichment when the equity has increased with money, things or goods but also when they have been canceled or extinguished debt obligations. Also, the COIP referred in his Book I, Title IV, Chapter V, Section Five, Article 298, - for tax fraud, says:  The person who simulate, hide, ignore, distort or mislead in determining the tax liability, to stop paying all or part of the taxes actually due, for their own benefit or a third party. As seen in the previous analysis, in the COIP it considered crimes illicit enrichment and tax fraud, but it does separate, therefore, in recent times has emerged the need for typing and prosecution of the offense of illicit enrichment by the Tax evasion, as worldwide and particularly in Ecuador, there is an alarming increase in this type of crime, which has been further evidenced by the recent case of Panama Papers; why this topic of study and research, same general objective was chosen: Conduct a legal and doctrinal study to reform the Code of Criminal Integral, incorporating therein the offense of illicit enrichment by tax fraud. In itself the following objectives were defined:  Analyze and characterize Article 279 and 298 of the Code of Criminal Integral.  The offense of illicit enrichment by the Tax Fraud according to the general principles of Integral Penal Code.  Conduct a legal reform Comprehensive Organic Code of Criminal Procedure, which incorporates in it, the offense of illicit enrichment by the Tax Fraud. To develop the specific objectives we use several methods, such as scientific, analytical, inductive and deductive, plus several techniques such as direct observation, interview and survey was handled; same that allowed us to gather relevant information for this investigation. For the development of this thesis, he polled 30 professionals free exercise of the right and interviewed an honest professional matter for comment on the problems in analysis, thus relevant information tabulated was obtained, it was represented in statistical tables and it was interpreted; also the most important cases related to this study, after this conceptual and legal theoretical information was compiled, which allowed us to compare the results and make a proposal to reform the Code of Criminal Integral to incorporate the crime of illicit enrichment by analyzed the Tax evasion. Finally the conclusions and most important recommendations that helped to determine the results of this investigation were determined.